EFFECTS OF SPRAYING CEMELE PEPPER (Capsicum annuum L.) EXTRACTS ONTO HATCHING EGGS OF ATAK-S LAYER HENS ON HATCHING RESULTS, SERUM GLUTATHIONE AND MALONDIALDEHYDE LEVELS - Fatma ERGÜN; Atilla TASKIN; Demirel ERGÜN (Journal of Animal and Plant Sciences, 2024)
Alternative natural products have been used in hatching since chemicals used in the incubation of chicken eggs have toxic effects on the embryo, the practitioners and the environment. In this study with completely randomized design (CRD) the effects of a registered local pepper (Cemele) extract at different dosages in the incubation process of hatching eggs was examined. The chloride group disinfectant (T1), ethanol (T2), 2% pepper extract (T3), and 4% pepper extract (T4) were sprayed on to disinfect eggs before the incubation process. On the second, eighth, and eighteenth incubation days of the groups, the total mesophilic aerobic bacteria (TMAB) loads of the eggshell were examined, and the lowest load values were found at T4. In this study, the highest hatching efficiency (H) and the highest fertilised hatching rate (HF) were 87.52±2.88% and 81.66±1.44%, respectively, in T4. Early embryonic mortality (EEM) was not observed at T4, while the highest value was 7.11±1.35% at T2. The highest mid embryonic mortality (MEM) rate was 10.91±0.34% in T3 while the lowest rate was 7.11±1.35% in T4. The late embryonic mortality (LEM) rates were 14.22±2.69% in T2, 12.47±1.17% in T1, 12.66±2.69% in T3 and 5.30±0.17% in T4. The lowest malposition rate 8.92±0.01% and the lowest malformation rate 8.83±0.12% were observed in T4. At the end of this study, body weights, lengths, tona, and pasgar scores of the hatched chicks were calculated. The highest body weight and length values were observed as 43.57±1.37 g and 16.47±0.45 cm in T4 birds, respectively. The highest tona score was 98.10±1.27 in T4 and the lowest tona score was 93.65±1.22 in T1 birds. Pasgar score values of the chicks were 9.69±0.16 in T4, 9.38±0.17 in T2, 9.31±0.18 at T3 and 9.16±0.16 in T1, respectively. The MDA values of birds were 8.63±0.05, 0.70±0.10, 0.28±0.01 and 0.25±0.01 nmol mL-1 in T1, T2, T3 and T4, respectively while the highest GSH value was 32.39±0.66 mM in T4, and the lowest value 11.15±1.03 mM in T2. In conclusion, the use of Cemele pepper extract had positive results in the incubation process of hatching eggs.
Keywords: Incubation process; disinfectant; chlorine dioxide; ethanol; cemele pepper